2021
DOI: 10.1038/s41433-021-01614-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical electrophysiology of the optic nerve and retinal ganglion cells

Abstract: Clinical electrophysiological assessment of optic nerve and retinal ganglion cell function can be performed using the Pattern Electroretinogram (PERG), Visual Evoked Potential (VEP) and the Photopic Negative Response (PhNR) amongst other more specialised techniques. In this review, we describe these electrophysiological techniques and their application in diseases affecting the optic nerve and retinal ganglion cells with the exception of glaucoma. The disease groups discussed include hereditary, compressive, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 239 publications
(233 reference statements)
1
17
0
Order By: Relevance
“…Under photopic conditions, additional measurements included the b-wave, which indirectly reflects the cone activity since the a-wave cannot be measured reliably, and the PhNR, a negative-going wave following the b-wave that originates in the inner retinal layer and is correlated with RGC activity [30]. As shown by photopic ERG responses in Figure 6D and quantitative analysis of b-wave and PhNR amplitudes in Figure 6E,F, in untreated LD rats, the photopic b-wave (LD 19.20 ± 2.95 µV, p < 0.0001) and the PhNR (LD 11.40 ± 2.30 µV, p < 0.0001) were both reduced in amplitude compared to control (control b-wave 50.00 ± 6.78 µV; PhNR 30.00 ± 2.91 µV).…”
Section: Combined Efficacy Of Lutein and C3g On Retinal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under photopic conditions, additional measurements included the b-wave, which indirectly reflects the cone activity since the a-wave cannot be measured reliably, and the PhNR, a negative-going wave following the b-wave that originates in the inner retinal layer and is correlated with RGC activity [30]. As shown by photopic ERG responses in Figure 6D and quantitative analysis of b-wave and PhNR amplitudes in Figure 6E,F, in untreated LD rats, the photopic b-wave (LD 19.20 ± 2.95 µV, p < 0.0001) and the PhNR (LD 11.40 ± 2.30 µV, p < 0.0001) were both reduced in amplitude compared to control (control b-wave 50.00 ± 6.78 µV; PhNR 30.00 ± 2.91 µV).…”
Section: Combined Efficacy Of Lutein and C3g On Retinal Functionmentioning
confidence: 99%
“…In this respect, the extracellular currents that generate the b-wave either originate directly in ON-bipolar cells or reflect potassium-induced changes in the membrane potential of Müller cells enveloping them. In addition, the b-wave is also affected by light-induced activity in third-order retinal neurons (amacrine cells and RGCs) as demonstrated by the PhNR, a negative-going wave following the b-wave that originates in the inner retinal layer in response to photopic conditions and is correlated with RGC activity [30].…”
Section: Preventive Efficacy Of Antioxidant Compoundsmentioning
confidence: 99%
“…1 c). These results were suggestive for ganglion cell damage [4], however, they were still not crucial in differentiating NTG from NAION. Thus, in order to exclude permanent retinal vascular hypoperfusion or dysregulation, retinal vessel analyses were performed.…”
Section: Case Reportmentioning
confidence: 73%
“…Here, slightly reduced mfERG responses in the central and paracentral area of the left eye correlated with the ipsilateral slightly reduced P100 and N135 amplitudes of the pattern VEP. An interesting finding was also, however, the slightly prolonged P100 latencies for the smaller 7.5′ checkboard on the left eye, suggestive for ganglion cell damage [4]. Since the P100 latency was only slightly delayed, a possible optic nerve demyelination disorder was ruled out and pointed towards a vascular event of the optic nerve.…”
Section: Discussionmentioning
confidence: 95%
“…In optic neuritis, the loss of axons caused by the process of demyelination leads to severe dysfunction, which is closely related to changes in the visual field and the thickness of the RNFL [52,53]. Several studies in an experimental autoimmune disease model reported that inflammatory cells released a neurotoxic cytokine attack against the myelin sheath, resulting in further loss of RGCs in apoptosis [54,55].…”
Section: Discussionmentioning
confidence: 99%